The Role of Interfaith Dialogue in Completing the Construction of Worship Place (Efforts to Keep the Spirit of Nationalism) - Halena Artamevia; Aurelia Jessica Mavelyn; Sherly Surjady; Barnabas Juni Saputra Gulo (PT ARRUS Intelektual Indonesia, 2023)
Interfaith dialogue is a discussion or exchange of certain information between followers of various religions as a way to achieve cooperation of common interests. Religious or faith dialogue has an important role to form a spirit of nationalism and prevent intolerance, which still often occurs in Indonesia, especially in religion aspect. One example of an intolerance religious case is the rejection of the construction related to a place of worship by followers of a particular religion and believers, citing concerns about damaging the image and culture of the area. Therefore, dialogue between religious communities is very necessary as a way to prevent intolerance. This dialogue aims to instill the value of tolerance and strengthen pluralism in Indonesia. The research methods employed in this problem are descriptive and normative research by conducting documentation and case studies that refer to primary and secondary legal sources supporting the study on the relationship between interfaith dialogue communities and the spirit of nationalism. The research findings indicate a correlation between these both aspects. Religion and nationality are two things that are interrelated between obstacles and support. Dialogue between religious communities is also a form of participation in religious values ​​that must be supported and maintained by both the government and Indonesian society in order to create tolerance, which is the beginning of the rise of the nationalism spirit.